Students’ behavioral intention on interactive video in primary Cinematography of Art Universities in Chengdu, China - Gao, Xuhan; Phongsatha, Thanawan (Scholar: Human Sciences, 2023)
The emergence of the COVID-19 has made some traditional classroom teaching impossible. Therefore, online teaching has become a compelling choice for higher education in China. However, the shortcomings of the weak sense of communication in online teaching leads to poor teaching quality. Especially in the cinematography major, as a highly practical major, online teaching methods cannot achieve the purpose of teaching. The emergence of interactive video technology has brought a turning point for this kind of practical professional network teaching. The study was to explore the effect of using interactive video in major cinematography classrooms and the acceptance of students. The theoretical basis of this research is the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Unified Theory of Acceptance and Use of Technology (UTAUT). The variables are perceived usefulness, perceived ease of use, attitude, social influence, self-efficacy, and behavioral intention. The 480 questionnaires were distributed to students from three universities. The data analysis was based on 451 valid questionnaires returned. The Structural Equation Model (SEM) SEM was used to validate the research hypothesis to determine the relationship between variables. The findings indicate that all six hypotheses proposed in this study are supported. The results showed that students’ perceived ease of use when using interactive videos for learning directly affect their perceptions on the usefulness of interactive videos. Perceived ease of use and perceived usefulness directly impact attitude; that is, when students perceived that the interactive video is easy to operate or helpful, it positively affect their attitude towards interactive video. In addition, attitude, self-efficacy, and social influence are the three influencing factors in predicting students’ behavioral intentions. The research results would promote the widespread use of interactive video in higher education by investigating cinematography students’ behavioral intentions to use interactive video in professional.